1998
DOI: 10.1039/a805853i
|View full text |Cite
|
Sign up to set email alerts
|

A study of iodine loss during the preparation and analysis of samples using 131I tracer and neutron activation analysis

Abstract: The recoveries of various species of iodine, such as I 2 , IO 3 2 and organic iodine, in the procedures of acid digestion, ashing, freeze-drying, evaporation drying and neutron irradiation were studied using 131 I tracer and instrumental neutron activation analysis. The recoveries of iodine were over 99% after drying at room temperature and 60-80 °C for various iodine species in all kinds of media. The organic iodine in various media, I 2 and IO 3 2 in biological materials and IO 3 2 in alkaline solution were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Under optimum conditions of 650 °C for ashing temperature and a 0.2-0.3 weight ratio of KOH to sample, 70-85% of iodine can be recovered in the leachate. 26 In this work, a recovery as high as 98% was observed for seaweed samples; it probably resulted from the high iodine concentration (more than 100 mg g 21 ) in seaweed. The total recovery of iodine, including extraction, ranges from 60 to 65% for grass samples and 85 to 97.5% for seaweed samples.…”
Section: Separation Of Iodine From Vegetation and Soil Samplesmentioning
confidence: 53%
See 2 more Smart Citations
“…Under optimum conditions of 650 °C for ashing temperature and a 0.2-0.3 weight ratio of KOH to sample, 70-85% of iodine can be recovered in the leachate. 26 In this work, a recovery as high as 98% was observed for seaweed samples; it probably resulted from the high iodine concentration (more than 100 mg g 21 ) in seaweed. The total recovery of iodine, including extraction, ranges from 60 to 65% for grass samples and 85 to 97.5% for seaweed samples.…”
Section: Separation Of Iodine From Vegetation and Soil Samplesmentioning
confidence: 53%
“…The analytical methods for grass and seawater have been described in detail elsewhere. 25,26 For soil samples, 0.5 ml of separated iodine solution (see section 1.2.2) was taken and sealed in a half-dram polyvial. The iodine content was determined by radiochemical NAA.…”
Section: Determination Of 127 I In Grass Seawater and Soil Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of 129 I was derived from the isotopic ratio using the concentration of stable iodine and chemical yield for iodine separation determined from ICP-MS. Only the chemical yield of the first step, namely leaching of air filters by reflux heating in alkaline medium could not be controlled. According to Hou et al, loss of iodine at pH 9e10 and 60e80 C is negligible (Hou et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In kelp species, the iodine accumulates naturally in the extracellular matrix in the form of iodide (I -) which readily scavenges a variety of reactive oxygen species (ROS) from both aqueous and gaseous oxidants (Küpper et al 2008). A study from Hou et al (1998) reported reduced recovery of iodide in aqueous solutions following freezedrying (30 to 40%) compared to air-drying (100%) although a similar effect of freeze-drying on the recovery of iodide directly from seaweed material was not observed. However, the chemical species of iodine are known to differ among seaweeds and no mention is made of the species used in this study.…”
Section: Nutrient Contentmentioning
confidence: 99%